Inhibition of Taq DNA polymerase by iridoid aglycone derivates - Pungitore, C. R.; García, C.; Sotero Martín, V.; Tonn, C. E. (Cellular and Molecular Biology, 2012)
Faithful replication of DNA molecules by DNA polymerases is essential for genome integrity and correct transmission of genetic information in all living organisms. DNA polymerases have recently emerged as important cellular targets for chemical intervention in the development of anti-cancer agents. Herein we report additional synthesis of simplified bicyclic aglycones of iridoids and their biological activity against Taq DNA polymerase with the object to find out some of the likely molecular targets implicated in the biological activity showed for this kind of compounds. The compounds 14, 33 and 34 showed inhibitory activity against Taq DNA polymerase with IC50 values of 13.47, 17.65 and 18.31 µM, respectively. These results would allow proposing to DNA polymerases as the molecular targets implicated in this bioactivity and enhance the iridoid aglycones as leader molecule to develop new drugs for cancer therapy.